P, Perancangan PERANCANGAN ALAT SISTEM KONTROL KELEMBAPAN TANAH MENGGUNAKAN MIKROKONTROLER ESP8266 DAN SENSOR SOIL MOISTURE DI KAKTUS THREED LEMBANG - Irman Hariman (Jurnal Teknologi Informasi, 2022)
Abstract There are many technologies that have been developed to meet the needs of human life, one of which is the smart greenhouse. Smart greenhouse is a building that is closed and equipped with automatic system equipment. In general, sunlight will not fully enter the greenhouse, this has a bad impact on the plants inside, especially for greenhouses that provide cactus plants. Soil moisture is water that fills all soil pores above the ground water surface. The use of soil moisture is as a water resource, drought early warning and irrigation planning. Lack of water in soil moisture can cause plant wilting. Based on this explanation, research was made with the theme of designing a soil moisture measuring instrument using a YL-69 soil moisture sensor using an ESP8266 microcontroller. This tool is connected to the android application as an interface medium to display the measured soil moisture value. The purpose of making this tool is to make it easier to monitor and control soil moisture. A maximum 200 word abstract in English in italics with Times New Roman 11 point. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief.